2022
DOI: 10.1126/sciimmunol.abn3800
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency, autoimmunity, and increased risk of B cell malignancy in humans with TRAF3 mutations

Abstract: Tumor necrosis factor receptor–associated factor 3 (TRAF3) is a central regulator of immunity. TRAF3 is often somatically mutated in B cell malignancies, but its role in human immunity is not defined. Here, in five unrelated families, we describe an immune dysregulation syndrome of recurrent bacterial infections, autoimmunity, systemic inflammation, B cell lymphoproliferation, and hypergammaglobulinemia. Affected individuals each had monoallelic mutations in TRAF3 that reduced TRAF3 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…Mice lacking TRAF3 in all mature T cells (T-Traf3 −/− ) have normal T, B, and myeloid cell numbers but mount poor CD4 + and CD8 + T cell responses to infection by the intracellular bacterium Listeria monocytogenes and cannot produce a T cell-dependent humoral response to immunization (22). Many of the functional defects exhibited by TRAF3deficient T cells originate with defective TCR signaling, which we described in T-Traf3 −/− mouse T cells and which was corroborated in human patients with one mutated TRAF3 allele (22,26). A major role of TRAF3 in promoting TCR function is to interfere with negative regulators of early TCR signals.…”
Section: Introductionsupporting
confidence: 72%
“…Mice lacking TRAF3 in all mature T cells (T-Traf3 −/− ) have normal T, B, and myeloid cell numbers but mount poor CD4 + and CD8 + T cell responses to infection by the intracellular bacterium Listeria monocytogenes and cannot produce a T cell-dependent humoral response to immunization (22). Many of the functional defects exhibited by TRAF3deficient T cells originate with defective TCR signaling, which we described in T-Traf3 −/− mouse T cells and which was corroborated in human patients with one mutated TRAF3 allele (22,26). A major role of TRAF3 in promoting TCR function is to interfere with negative regulators of early TCR signals.…”
Section: Introductionsupporting
confidence: 72%
“…Future research including studies in mice is required to investigate a potential causal role of GTF3A mutations in the dysfunction of other immune system components and the other clinical presentations observed. In line with this notion, recent work on TRAF3 deficiency, initially described as a genetic etiology of HSE ( 48 ), has now been associated with B cell dysfunction in patients exhibiting an immune dysregulation syndrome ( 49 ).…”
Section: Discussionmentioning
confidence: 90%
“…This is corroborated by frequent TRAF3 mutations detected in canine non-Hodgkin lymphomas (NHL) (31)(32)(33)(34). Similar to Traf3 -/mouse B cells, human B cells with germline TRAF3 mutations that reduce TRAF3 expression also exhibit constitutive NF-kB2 activation and enhanced responses to BCR, BAFF, TLR9, and IL-6 signaling, including increased proliferation and plasma cell formation associated with elevated activation of NF-kB1, ERK, AKT, and STAT3 (14). Reconstitution of TRAF3 expression in TRAF3-defi c ient human MM cells induces apoptosis, demonstrating a tumor suppressive role of TRAF3 in B cell malignancies (9,35).…”
Section: Traf3 In B Cell Biology and B Cell Malignanciesmentioning
confidence: 84%
“…The first germline mutation of TRAF3, an autosomal loss-of-expression mutation (R338W), was initially reported in a patient with a history of herpes simplex virus-1 (HSV-1) encephalitis (12) and also detected in another patient with recurrent Mycobacterium abscessus infection (13). Interestingly, heterozygous germline mutations in TRAF3 (premature stop codon mutations) were recently identified in 9 patients from five unrelated families, causing an immune dysregulation syndrome characterized by recurrent bacterial infection, autoimmunity, systemic inflammation, B cell lymphoproliferation, and hypergammaglobulinemia (14). Furthermore, genome-wide association studies (GWAS) and targeted analyses demonstrated that common genetic variants of TRAF3, which reduce TRAF3 expression, are associated with an increased risk of B cell malignancies, systemic lupus erythematosus, hypergammaglobulinemia, and recurrent bacterial infection in a wider population (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation